BINARY LOGISTIC REGRESSION IN DETERMINING AFFECTING FACTORS STUDENT GRADUATION IN A SUBJECT - Shedriko Shedriko (Universitas Islam Kuantan Singingi, 2021)
Good communication and coordination between lecturers are needed in delivering material by different lecturers to ensure the relatively uniform quality of education. Knowing the success information from several classes to predict other classes, should be completed by significant parameters used in the algorithm. This research is using a quantitative analysis method with binary logistic regression methodology in determining critical factors of train data on “Introduction to Information Technology” subject in the university of XYZ. Several statistical testing are conducted to give the expected results using software excel with Real Statistics add-ins and Orange Data Mining in testing the pass-prediction from the given data training. The successive model can also be used to classify graduation for the different subjects.